Re-intermediation of the crypto asset ecosystem by banks: An empirical study on acceptance drivers among the populace - Christian Zeiß; Myriam Schaschek; Lisa Straub; Christoph Tomitza; Axel Winkelmann (Electronic Markets, 2024)
After the initial surge in decentralized finance, widespread public adoption did not materialize. A predominant portion of the populace harbors distrust towards the crypto asset market. Conversely, banks, serving as intermediaries in financial management, enjoy heightened trust. The contemporary development within the banking sector indicates an inclination towards integrating into the crypto asset market. This integration results in new business models for banking institutions and emergent opportunities for their clientele. Prior research addresses perceptions surrounding cryptocurrencies. The present research augments this field by investigating the acceptance of crypto assets. Specifically, we conducted an empirical user study to analyze investing behaviors. By adapting the theoretical framework of the technology acceptance model to the unique characteristics of crypto assets, we highlight acceptance drivers. Notable variances in awareness of crypto assets affect investment decisions. The findings of this study contribute to social welfare by identifying impediments to sustainable investment practices. Additionally, these insights facilitate a more sophisticated comprehension of strategic alternatives available to banking institutions.
Keywords: G11; G41; G21; 620; Crypto assets; Digital assets; Acceptance; Investment banking; DeFi; Blockchain